2017
DOI: 10.1038/srep43198
|View full text |Cite
|
Sign up to set email alerts
|

Increased 4R tau expression and behavioural changes in a novel MAPT-N296H genomic mouse model of tauopathy

Abstract: The microtubule-associated protein tau is implicated in various neurodegenerative diseases including Alzheimer's disease, progressive supranuclear palsy and corticobasal degeneration, which are characterized by intracellular accumulation of hyperphosphorylated tau. Mutations in the tau gene MAPT cause frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17). In the human central nervous system, six tau isoforms are expressed, and imbalances in tau isoform ratios are associated with pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…We found that vehicle-treated Tg mice displayed a marked increase in locomotor and exploratory activity during the initial habituation to the test environment and the dark phase of their activity cycle. This higher activity level, which was corrected by selenate treatment, is reminiscent of reports of hyperactivity in other Tau mouse models such as P301S (Przybyla et al, 2016 ), rTg4510 (Joly-Amado et al, 2016 ; Jul et al, 2016 ; Blackmore et al, 2017 ; Wang et al, 2018 ), MAPT-N296H (Wobst et al, 2017 ), N279K (Taniguchi et al, 2005 ) and a triple repeat mutant tau transgenic mouse line (Rockenstein et al, 2015 ). Of note, a Mapt −/− model on a B6129PF3/J genetic background also displayed hyperactive behavior (Biundo et al, 2018 ).…”
Section: Discussionsupporting
confidence: 61%
“…We found that vehicle-treated Tg mice displayed a marked increase in locomotor and exploratory activity during the initial habituation to the test environment and the dark phase of their activity cycle. This higher activity level, which was corrected by selenate treatment, is reminiscent of reports of hyperactivity in other Tau mouse models such as P301S (Przybyla et al, 2016 ), rTg4510 (Joly-Amado et al, 2016 ; Jul et al, 2016 ; Blackmore et al, 2017 ; Wang et al, 2018 ), MAPT-N296H (Wobst et al, 2017 ), N279K (Taniguchi et al, 2005 ) and a triple repeat mutant tau transgenic mouse line (Rockenstein et al, 2015 ). Of note, a Mapt −/− model on a B6129PF3/J genetic background also displayed hyperactive behavior (Biundo et al, 2018 ).…”
Section: Discussionsupporting
confidence: 61%
“…Surprisingly, most of the skipped exons occurred in genes that have pre-synaptic functions such as synaptic vesicle recycling, transport, and exocytosis, which could at least partially explain alterations in synaptic vesicle dynamics and neurotransmitter release in FXS model mice (Deng et al, 2013;Ferron et al, 2014;Broek et al, 2016). Furthermore, a number of skipped exons in Fmr1 KO have been linked to neurological disorders such as autism (skipped microexon 4 in Cpeb4; Irimia et al, 2014;Parras et al, 2018;Quesnel-Vallie `res et al, 2016), Alzheimer's disease (skipped exon 7 in APP; Fragkouli et al, 2017;Rockenstein et al, 1995), Parkinson's disease (skipped exon 3 in Mapt; Lai et al, 2017;Wobst et al, 2017), and intellectual disabilities (skipped exon 12 in Cnksr2; Houge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory uses high capacity bacterial and P1-phage artificial chromosome vectors (BACs and PACs) to express whole genomic loci in culture and applies homologous recombination technology to manipulate the large inserts with base-pair accuracy. We have previously used these vector systems to express the human MAPT locus in neuronal cell culture models and demonstrated MAPT locus expression is under developmental and cell-type specific regulation [ 26 ] and in transgenic mouse models express all six adult tau isoforms [ 27 ]. Here, we applied an analogous strategy to generate genomic DNA p MAPT -H1 and p MAPT -H2 expression vectors with identical upstream and downstream sequence, differing only at sites of haplotype variation.…”
Section: Introductionmentioning
confidence: 99%